2005
DOI: 10.1016/j.jet.2004.05.010
|View full text |Cite
|
Sign up to set email alerts
|

On Ramsey's conjecture: efficient allocations in the neoclassical growth model with private information

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…As Ψ * is a continuous, compact-valued, and convex correspondence, the set of constrained efficient plans can be parameterized by Welfare weights (θ 1 , θ 2 ) ∈ R 2 + (Espino, 2005). We say that (C * , K * ) is constrained efficient if it is the corresponding plan sustaining the levels of lifetime utility that solves…”
Section: Modelmentioning
confidence: 99%
“…As Ψ * is a continuous, compact-valued, and convex correspondence, the set of constrained efficient plans can be parameterized by Welfare weights (θ 1 , θ 2 ) ∈ R 2 + (Espino, 2005). We say that (C * , K * ) is constrained efficient if it is the corresponding plan sustaining the levels of lifetime utility that solves…”
Section: Modelmentioning
confidence: 99%
“…3 Differences in discount factor might be more misleading. In that case, it can be shown that the limiting distribution of consumption will concentrate full mass in the relatively patient agent (see Espino [2005] To study asset trading volume, we need to compute equilibrium portfolios. But solving the problem directly is difficult.…”
Section: The Economymentioning
confidence: 99%
“…We will not discuss the well-known equivalence results between the allocations and prices corresponding to the following market structures with sequential trading and the previously discussed ADCE allocations and prices. 6 To study different complete market structures, we first present the general frame- is one outstanding share for each firm and then P i θ ij (s t ) = 1 for all s t and j. 7 We do not impose short selling constraints however.…”
Section: Sequential Trading and Recursive Competitive Equilibriummentioning
confidence: 99%
“…Among these, the closest work is by Bohacek (2005), who provides conditions under which an economyà la Atkeson and Lucas (1995) admits a stationary and ergodic distribution of consumption. Other papers in this class include Marcet and Marimon (1992), Khan and Ravikumar (2001), and Espino (2005).…”
Section: Introductionmentioning
confidence: 99%